Optimal Time of Tracheotomy in Infants: Still a Dilemma. (30th January 2015) - Unal, Sevim; Bilgin, Leyla Karadeniz; Gonulal, Deniz; Akcan, Fatih Alper
Objective . Infants with respiratory failure may require prolonged intubation. There is no consensus on the time of tracheotomy in neonates. Methods . We evaluated infants applied tracheotomy, time of procedure, and early complications in our neonatal intensive care unit (NICU) retrospectively from January 2012 to December 2013. Results . We identified 9 infants applied tracheotomy with gestational ages 34 to 41 weeks. Their diagnoses were hypotonic infant, subglottic stenosis, laryngeal cleft, neck mass, and chronic lung disease. Age on tracheotomy ranged from 4 to 10 weeks. Early complication ratio was 33.3% with minimal bleeding (1), air leak (1), and canal revision requirement (1). We discharged 7 infants, and 2 infants died in the NICU. Conclusion . Tracheotomy makes infant nursing easy for staff and families even at home. If carried out by a trained team, the procedure is safe and has low complication. When to apply tracheotomy should be individualized, and airway damage due to prolonged intubation versus risks of tracheotomy should be taken into consideration.